Evaluation of eosinophil count and neutrophil-lymphocyte count ratio versus C-reactive protein levels in patients with sepsis - Khajuria, Rahul; Jamwal, Vinu; K. Gupta, Anil; Gupta, Abhinav (International Journal of Research in Medical Sciences, 2017)
Background: One major problem encountered in the intensive care unit is differentiating the inflammatory response from an infective process. Clinical and standard laboratory tests are not very helpful because most critically ill patients develop some degree of inflammatory response, whether or not they have sepsis. Numerous biomarkers have been evaluated to predict mortality in critically ill patients, although none have proved entirely useful. Objective of the study was to evaluate eosinophil count and neutrophil-lymphocyte count ratio with C-reactive protein levels in patients with sepsis. Methods: 71 patients >18 years of age of either sex with a diagnosis of sepsis were enrolled in this one-year observational study. Patients were classified according to the criteria of the American College of Chest Physicians/Society of Critical Care Medicine into sepsis group (n=50) and no sepsis group (n=21). Sepsis group were further divided into subgroups: sepsis (n=19), severe sepsis (n=16) and septic shock (n=15). Absolute eosinophil cell, neutrophil and lymphocyte counts for first 4 consecutive days and then on alternate days up to one week were also noted down. C-reactive protein levels on day 3 were also noted down. Results: In the sepsis group, mean eosinophil count was significantly (p<0.0001) low, mean neutrophil/lymphocyte count ratio was significantly (p<0.0001) high, mean CRP count was significantly (p=0.019) more as compared to that of no sepsis group. Among 16 mortalities, significant (p<0.05) decrease was noted in mean eosinophil count from day 3 onwards in patients of sepsis and septic shock subgroups. Mean N/L ratio showed no significant difference in patients of sepsis, severe sepsis or septic shock. Mean CRP count showed significant (p<0.05) increase in severe sepsis patients and mean Apache II score showed significant (p<0.05) deterioration in patients of septic shock. Conclusions: Neutrophil/lymphocyte count ratio (NLCR) and absolute eosinophil count (AEC) came out as better independent biomarker of sepsis in critically ill patients with infection admitted in intensive care unit. Diagnostic performance was better in these two diagnostic markers as compared to CRP marker. NLCR presented with sensitivity of 89.58%, AEC with 82.35% and CRP with 80.77%. Outcomes of NLCR and AEC were quick, easy and economical in establishing diagnosis of sepsis.